2016
DOI: 10.1002/jobm.201600478
|View full text |Cite
|
Sign up to set email alerts
|

Coconut oil induced production of a surfactant-compatible lipase fromAspergillus tamariiunder submerged fermentation

Abstract: Filamentous fungi are efficient producers of lipases. The present study focuses on identification of a potent lipolytic fungus and enhancement of lipase production through optimization of nutritional and cultural conditions under submerged fermentation. Molecular characterization of the fungus by 18S rDNA sequencing revealed its identity as Aspergillus tamarii with 98% homology. Maximum lipase production was noted in mineral salts medium supplemented with coconut oil (2.5%, v/v). A combination of ammonium chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
1
10
1
1
Order By: Relevance
“…Therefore, in the present study, we aimed to estimate and establish the required concentrations of selected variables. A significantly high lipase activity of 3.93 (U/ml) recorded with POME could be due to the presence of high content of saturated fatty acids [16]. This is in accordance with the studies of Salihu et al [52], where POME upon addition to other production components was identified to greatly enhance the lipase production by Penicillium citrinum .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Therefore, in the present study, we aimed to estimate and establish the required concentrations of selected variables. A significantly high lipase activity of 3.93 (U/ml) recorded with POME could be due to the presence of high content of saturated fatty acids [16]. This is in accordance with the studies of Salihu et al [52], where POME upon addition to other production components was identified to greatly enhance the lipase production by Penicillium citrinum .…”
Section: Discussionsupporting
confidence: 89%
“…The variation in medium components as well as their concentrations has been found to influence fungal lipases production greatly [16], [25]. Therefore, in the present study, we aimed to estimate and establish the required concentrations of selected variables.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Ao analisar a literatura, vários autores reportam a produção de lipases por fungos em cultivo submerso suplementado com diferentes óleos. Lima et al (2003) Por fim, no estudo de Das et al (2016), com a finalidade de encontrar as melhores condições nutricionais e demais condições para a cultura de Aspergillus tamarii crescer e produzir lipase, foi observado a eficiência do óleo de coco para a fermentação submersa.…”
Section: Influência Das Fontes De Carbono Para a Produção De Lipase Eunclassified